1997
DOI: 10.1124/mol.52.3.524
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Human α4β2 Neuronal Nicotinic Acetylcholine Receptors by Cholinergic Channel Ligands and Second Messenger Pathways

Abstract: The alpha4beta2 nicotinic acetylcholine receptors (nAChRs), a major subtype in the brain, have been shown to be modulated by chronic treatment with nicotine. In this study, the regulation of recombinant human alpha4beta2 nAChR subtype by (-)-nicotine and other cholinergic channel modulators was studied using human embryonic kidney 293 cells stably expressing this subunit combination. The treatment of transfected cells with (-)-nicotine and other activator ligands, including (-)-cytisine, 1,1-dimethyl-4-phenylp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
124
3
1

Year Published

2000
2000
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(144 citation statements)
references
References 29 publications
16
124
3
1
Order By: Relevance
“…The Western blot analysis demonstrated the up-regulation of ␣ 4 /␤ 2 nnAChRs after the long term exposure of the neurons to 0.1 M nicotine. These data are in good agreement with the previous reports using human embryonic kidney cells (14) and Xenopus oocytes (15), although in the latter study the induction of up-regulation of ␣ 3 /␤ 4 nnAChRs required a 10-fold higher nicotine concentration for up-regulating ␣ 4 /␤ 2 nnAChRs (15).…”
Section: Casupporting
confidence: 83%
See 2 more Smart Citations
“…The Western blot analysis demonstrated the up-regulation of ␣ 4 /␤ 2 nnAChRs after the long term exposure of the neurons to 0.1 M nicotine. These data are in good agreement with the previous reports using human embryonic kidney cells (14) and Xenopus oocytes (15), although in the latter study the induction of up-regulation of ␣ 3 /␤ 4 nnAChRs required a 10-fold higher nicotine concentration for up-regulating ␣ 4 /␤ 2 nnAChRs (15).…”
Section: Casupporting
confidence: 83%
“…Among various regions of the central nervous system, the ␣ 3 , ␣ 4 , ␤ 2 , and ␤ 4 subunits of nnAChRs are unequally distributed in the different layers of the cerebral cortex (60), and several investigations have reported that the up-regulation of the receptors is due to the increased numbers of ␣ 4 /␤ 2 , ␣ 3 /␤ 4 , and ␣ 7 nnAChR subunits in neurons and nonneuronal expression systems (13,17,61). In addition to these data, nnAChRs composed with ␣ 4 /␤ 2 are adequately activated by nicotine at concentrations less than 10 - 100 nM (13) and also have been reported to show up-regulation after long term nicotine treatment (13)(14)(15)18). Based on these data, we attempted to examine which of the ␣ 3 , ␣ 4 , and ␤ 2 subunits showed up-regulation under the conditions used in the present study.…”
Section: Camentioning
confidence: 77%
See 1 more Smart Citation
“…Thus, a common pharmacological spectrum for up-regulation and high affinity binding is observed. Moreover, a correlation between the ligand binding concentrations and those required to upregulate has been observed (16,17,46,48). In our opinion, this suggests that the binding site for up-regulation corresponds to a low affinity conformation of the classical binding site that bridges the interface between the ␣ and ␤ subunits.…”
Section: Different Contributions Of the ␣ And ␤ Subunits To The Upregmentioning
confidence: 88%
“…A wide range of agonists specific for the binding site, such as nicotine, epibatidine, carbamylcholine, cytisine, dimethyl phenyl piperazinium (12,15,16,46,47), and even in some cases antagonists such as d-tubocurarine and dihydro-␤-erythroidine (14,46) have been shown to promote up-regulation of heteromeric receptors expressed in cell lines. Thus, a common pharmacological spectrum for up-regulation and high affinity binding is observed.…”
Section: Different Contributions Of the ␣ And ␤ Subunits To The Upregmentioning
confidence: 99%